PRACTICAL STRATEGIES FOR MANAGING ELEMENTARY CLASSROOMS EFFECTIVELY (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This paper investigates forward-looking methods of incorporating the awareness of global problems in the university EFL teaching through the implementation of three nicely devised, project-based activities. It is based on the theoretical frameworks of global citizenship education, project-based learning, multimodal pedagogy, and communicative language teaching, and the writer claims that learning a language would be a lot more fun and effective if the learners were doing it in the context of real global issues. The author describes three innovative classroom projects - The Future Museum, Global Problems Start-Up Pitch, and Voices from the Planet Documentary - and discusses their role in developing linguistic skills and simultaneously fostering critical thinking, creativity, and social responsibility.